An assessment of preretirement for planning for income adequacy by Oklahoma Public School teachers and administrators / - Marshall, Carolyn Martin (My University, 1984)
The primary problem of this study is to assess the extent of preretirement financial planning among Oklahoma Public School teachers and administrators age 45 years and older. The major objectives of the study were to examine the dimensions of financial planning for retirement, the attitudes or perceptions of financial adequacy for retirement, and specific demographic factors affecting preretirement planning.

A questionnaire containing 44 items was designed to elicit information. From the 300 surveys mailed to selected personnel in the Oklahoma Public Schools, 168 surveys were returned, which represents a 56 percent return rate. A preretirement score and a perception score was processed for each respondent. With these scores a Pearson Product Moment Correlation was computed to determine the relationship between the scores. The results at both .05 and .01 level were significant.

Major findings from this study were: (1) One hundred percent of the respondents indicated that most people should plan for retirement, while 83.9 percent had actually begun retirement planning. (2) An ANOVA performed on the data indicated a significant relationship between preretirement planning and average family monthly income. (3) The savings rate most frequently chosen to represent this group was 11 to 20 percent of gross monthly family income. (4) The method of investment most frequently chosen was annuities. (5) Only 73.8 percent of the participants were utilizing tax-advantage investments. (6) Only 26.2 percent of the respondents felt they would need 81 to 100 percent of their present income during retirement. (7) The median income level was in the category between $3,000 to $3,499 monthly gross earnings representing an annual income between $36,000 and $41,988. (8) Most of those surveyed indicated their retirement income would be Oklahoma Teachers' Retirement and Social Security. (9) Only 10 percent of those surveyed had been involved in any preretirement education. (10) The most popular topics of interests for preretirement education were: household budgeting and management, financial investment planning, estate planning, and recreational planning. (11) Sixty-one percent were tithing.
An assessment of pretirement planning for income adequacy ...
Keywords: Education, Business.